Passive synthetic aperture imaging with limited noise sources. (29th July 2016) - Garnier, Josselin
Abstract: We consider a passive synthetic aperture imaging problem. A single moving receiver antenna records random signals generated by one or several distant noise sources and backscattered by one or several reflectors. The sources emit noise signals modeled by stationary random processes. The reflectors can be imaged by summing the autocorrelation functions of the received signals computed over successive time windows, corrected for Doppler factors and migrated by appropriate travel times. In particular, the Doppler effect plays an important role and it can be used for resolution enhancement. When the noise source positions are not known, the reflector can be localized with an accuracy proportional to the reciprocal of the noise bandwidth, even when only a very small number of sources are available. When the noise source positions are known, the reflector can be localized with a cross range resolution proportional to the carrier wavelength and inversely proportional to the length of the receiver trajectory (i.e. the synthetic aperture), and with a range resolution proportional to the reciprocal of the bandwidth, even with only one noise source.